Research Status of 3-D Finite Element Simulation of Metal Cutting - Liu, Meng; Li, Guohe (Recent Patents on Engineering, 2018)
Background: The finite element method (FEM) has been widely applied in the research of metal machining which can improve the efficiency and reduce the cost of research. 3-D finite element simulation attracts more attention on the research of mechanism and parameter optimization of high-speed machining. Methods: This paper reviews the theses of 3-D finite element simulation in recent years, especially focuses on the key technology of FEM. Some application examples of 3-D finite element simulation in milling, turning and drilling are summarized. The differences of different types of simulation are compared and analyzed and the characters are concluded. In the end, the exiting problem and development direction of 3-D finite element simulation are also discussed. Besides, a lot of patents on 3D finite element simulation for metal machining were studied. Results: The key technology of FEM determines the accuracy of 3-D finite element simulation. And the finite element simulation of different types of processing can be realized by setting different contact and boundary conditions. Conclusion: FEM provides a new approach for the study of mechanism of metal machining. In order to improve the accuracy of 3-D finite element simulation, many researches focus on the improvement of the finite element model. The prediction results of finite element simulation can provide guidance for the parameter optimization of metal machining and the optimum design of tool. And the 3-D finite element simulation is hoped to be more accuracy and efficiency.
Keywords: key technology